Effect of Competence, Education and Training on Employee Performance with Work Motivation as Mediating Variable in Authority Office at Class II Airports in Papua and West Papua - Arief Santoso; Suratini; Mery Noviyanti (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2024)
This study aimed to determine the effect of competence, education and training on employee performance mediated by work motivation. The sample of this study consisted of all employees at the Authority Office of Class II Airports in Papua and West Papua, with a total of 160 people. The research instrument was a questionnaire with a 5-point Likert scale. The data obtained were then analyzed using path analysis with SPSS software version 24. The results showed that competence, education and training had a positive effect on work motivation and employee performance. Work motivation had a positive effect on employee performance and could mediate the effect of competence, education,and training on employee performance.